A pH responsive micelle combined with Au nanoparticles for multi-stimuli release of both hydrophobic and hydrophilic drug. Issue 63 (20th June 2016) - Lu, Qian; Meng, Yi-Fan; Gao, Peng-Cheng; Wei, Jing; Sun, Si; Zhou, Jian-Jun; Wang, Zhi-Fei; Jiang, Yong
Abstract : Spherical micelles self-assembled from PPMA- g -DNA interacted with ssDNA modified gold nanoparticles and the resulting hybrids may serve as nanocarriers for releasing both Nile red and DOX, which can be triggered by many stimuli. Abstract : Spherical micelles or nanofibers self-assembled from PPMA- g -DNA could be selectively achieved by tunning pH value. The spherical micelle could interact with ssDNA modified gold nanoparticles and the resulting hybrids may serve as nanocarriers for releasing both hydrophobic Nile red and hydrophilic doxorubicin hydrochloride (DOX), which could be triggered by many stimuli.